2017
DOI: 10.5296/jse.v7i4.12062
|View full text |Cite
|
Sign up to set email alerts
|

Preparing For Using Augmentative and Alternative Communication in Classrooms: Pre-Service Special Education Teachers’ Perceptions

Abstract: The purpose of this study was to examine pre-service special education teachers' perceptions regarding their skills and knowledge about the use of AAC, with respect to how well it prepared them to use AAC with students who have severe communication impairments. A descriptive research design was used to address the research questions. A total of 27 special education pre-service teachers (emphasized whether Early Childhood Special Education or Intellectual Disabilities) completed an online survey. The findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Several studies have indicated that some students with developmental and intellectual disabilities suffer from a deficiency in the process of language communication, resulting in multiple problems in educating and interacting with them ( Aldabas, 2017 ). This has necessitated the development of many augmentative and alternative communication methods ( Ahlgrim-Delzell et al, 2014 ) to help pupils who lack spoken language skills by identifying appropriate and the most effective communication tools and approaches with the relevant educational strategies based on the needs of such individuals ( Herberg et al, 2011 ; Ruwe et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have indicated that some students with developmental and intellectual disabilities suffer from a deficiency in the process of language communication, resulting in multiple problems in educating and interacting with them ( Aldabas, 2017 ). This has necessitated the development of many augmentative and alternative communication methods ( Ahlgrim-Delzell et al, 2014 ) to help pupils who lack spoken language skills by identifying appropriate and the most effective communication tools and approaches with the relevant educational strategies based on the needs of such individuals ( Herberg et al, 2011 ; Ruwe et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Augmentative and alternative communication includes all non-verbal communication methods for the purpose of encoding and exchanging messages. These approaches help individuals with severe communication disorders compensate for their inability to actively enhance their participation in various communicative interactions ( Wilder et al, 2015 ; Aldabas, 2017 ). These methods use diverse forms of communication such as gestures, body expressions, facial expressions, symbols, images, sound output devices, and other computer-based technologies in academic and social activities at school, home, and society ( Stancliffe et al, 2010 ; Mukhopadhyay and Nwaogu, 2013 ; Clinical Innovation and Governance, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation